1992
DOI: 10.1073/pnas.89.10.4447
|View full text |Cite
|
Sign up to set email alerts
|

Natural human antibodies to gamma interferon interfere with the immunomodulating activity of the lymphokine.

Abstract: Natural antibodies to y interferon (IFN-y) were found in patients suffering from different viral diae and, at a lower titer, in healthy individuals. Such antibodies were affinity-purified and studied for their capability to interfere in vitro with the antiviral and immunomodulating activity of IFN-y. Data obtained show that these human anti-IFN-y antibodies have no inhibitory effect on the antiviral activity of IFN-y. On the contrary, they are able to inhibit the expression of Fc receptor sites and HLA-DR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Turano et al (32) reported the presence of anti-IFN-γ antibodies in normal individuals that interfered with Fc receptor and HLA-DR expression but did not block antiviral activity. Madariaga et al (33) reported the presence of antibodies to IFN-γ in patients with M. tuberculosis infection, but their functional significance was not established.…”
Section: Discussionmentioning
confidence: 99%
“…Turano et al (32) reported the presence of anti-IFN-γ antibodies in normal individuals that interfered with Fc receptor and HLA-DR expression but did not block antiviral activity. Madariaga et al (33) reported the presence of antibodies to IFN-γ in patients with M. tuberculosis infection, but their functional significance was not established.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports describe pre-existing reactivity from antidrug antibody (ADA) assays in baseline samples collected from treatment-naïve subjects (1)(2)(3)(4)(5)(6)(7). This pre-existing reactivity can be due to the presence of antibodies from treatment-naïve subjects or due to other non-antibody interferents.…”
Section: Introductionmentioning
confidence: 99%
“…In HIV-infected patients, IFN-has been shown to be impaired, early in infection [20]. More recent reports describe increased IFN-production in virus-infected subjects [21], but in the serum of such patients high titred antibodies to IFN-were detected, able to interfere with the immunomodulating capacity, but not with the antiviral activity of the lymphokine [38,39]. In light of the above considerations the immunosuppressive activity of Ch7 might be even more effective in vivo in such patients.…”
mentioning
confidence: 99%